Risk assessment of the exposure of Spanish children to acrylamide using human biomonitoring. (15th July 2022) - Fernández, Sandra F.; Pardo, Olga; Coscollà, Clara; Yusà, Vicent; ,
Abstract: Acrylamide (AA) is an organic contaminant that naturally forms in starchy foods during high-temperature cooking under low-moisture conditions. It is mainly produced from the sugars and amino acids present in food by the Maillard reaction. When humans are exposed to AA, AA is eliminated in the urine as mercapturic acid conjugates, primarily including N-acetyl-S-(2-carbamoylethyl)-L-cysteine (AAMA), N-acetyl-S-(2-carbamoyl-2-hydroxyethyl)-L-cysteine (GAMA3), and N-acetyl-3-[(3-amino-3-oxopropyl)sulfinyl]-L-alanine (AAMA-Sul), which are used as exposure biomarkers of AA in human biomonitoring studies. Although the carcinogenic effects of AA on humans have not been demonstrated yet, some studies have shown that AA may negatively affect children's health. The main objective of this study was to evaluate the exposure of Spanish children (n = 612) to AA. For this purpose, the levels of AAMA, AAMA-Sul, and GAMA3 in first-morning urine samples were analyzed by "dilute and shoot" and liquid chromatography coupled to tandem mass spectrometry. The three metabolites were detected in all the children involved in this study in the following order (geometric mean (GM)): AAMA (79 ng ml −1 ) > AAMA-Sul (28 ng ml −1 ) > GAMA3 (18 ng ml −1 ). Statistical analysis suggested that the intake of fried potato products and biscuits could be associated with higher levels of AA metabolites in urine. Estimated daily intakes of AA in the children under study were in the range of 1.2–1.5 μg AA·kg-body weight −1 ·day −1 (GM). Risk assessment calculations indicate that the health risk of AA exposure cannot be overlooked and the exposure of Spanish children to AA should be closely monitored. Graphical abstract: Image 1 Highlights: Children urine samples showed quantifiable levels of all acrylamide metabolites. Mean levels of AAMA, AAMA-Sul, and GAMA3 were 79, 28, and 18 ng ml −1, respectively. Intake of fried potatoes and biscuits was a relevant contributor to acrylamide exposure. Estimated daily intakes of acrylamide were between 1.2 and 1.5 μg·kg-bw −1 ·day −1 . Risk assessment showed the need of reducing the exposure of children to acrylamide.